Post Infidelity Stress Disorder Found in Taylor Jenkin Reid's Malibu Rising - Laura Angelina; Linusia Marsih (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
The study aims to examine Post Infidelity Stress Disorder (PISD) in Taylor Jenkins Reid’s Malibu Rising. The discussion is focused on one of the characters in the novel, June. This study is a descriptive qualitative study with psychological approach. Psychological approach is applied due to the fact that this study concerns with the psychological motivation of the character in the novel. The result of the analysis shows that June has one criterion to be indicated as someone who tends to suffer from Post Infidelity Stress Disorder (PISD) i.e. dependent personality. June’s PISD are indicated through several symptoms ̶ exposure to a life threatening, experience of intense fear, hopelessness and horror, re-experiencing the event, avoidance of reminders of the event, emotional numbing, heightening anxiety, and irritability and rage. To deal with her PISD, she tries to avoid reminding the events that reminds her of her husband’s infidelity as the way to protect herself. June’s PISD affects her life and her children. She becomes addicted to alcohol and loses her physical health that eventually makes her die. Moreover, June’s PISD has also made her children change their attitude towards June. Her children are ashamed of her so that they always avoided her especially when they are in public places.